CONSUMING MOTHER IN DIANA RAZNOVICH'S CASA MATRIZ. - BROUGHAM, ROSE MARIE (Romance Notes, 2009)
A literary criticism is presented of the 1981 novel "Casa Matriz," by Diana Raznovich, particularly the mother-daughter relationship, consumerism, and gender stereotypes in the book. The plot and characters of the novel are described, especially the choice by the daughter, Bárbara to hire a woman to portray her mother. Other topics include the conception of mother as a commodity, the parodic aspects of the novel, and the philosopher Jean Baudrillard.